2018
DOI: 10.2136/sssaj2018.05.0196
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced‐Efficiency Fertilizer Impacts on Yield‐Scaled Nitrous Oxide Emissions in Maize

Abstract: Core Ideas Enhanced‐efficiency fertilizers reduced N2O compared with anhydrous ammonia in two of three years. SuperU reduced both area‐ and yield‐scaled N2O emissions in two of three years. Soil inorganic N concentrations were not correlated with daily N2O fluxes. Fertilizers ESN, SuperU, and UAN + nitrapyrin did not increase yield or grain N recovery efficiency. Balancing efforts to mitigate nitrous oxide (N2O) emissions from crop production while increasing grain yields is an important challenge for agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…While there is research that demonstrates the ability of EEF‐treated fertilizers to reduce N 2 O loss by as much as 32% (Eagle et al, 2017), details within the paper reveal that critical aspects necessary for EEF selection were not considered within the assumptions and calculations used to arrive at the concluded policy action. Rainfall, soil moisture, air temperature, and soil temperature can all impact the performance of nitrogen fertilizer treated with an EEF product (Barker and Sawyer, 2017; Eagle et al, 2017; Graham et al, 2018) and should be considered when assessing the environmental impact of EEF use.…”
Section: Examining the Kanter And Searchinger Papermentioning
confidence: 99%
See 4 more Smart Citations
“…While there is research that demonstrates the ability of EEF‐treated fertilizers to reduce N 2 O loss by as much as 32% (Eagle et al, 2017), details within the paper reveal that critical aspects necessary for EEF selection were not considered within the assumptions and calculations used to arrive at the concluded policy action. Rainfall, soil moisture, air temperature, and soil temperature can all impact the performance of nitrogen fertilizer treated with an EEF product (Barker and Sawyer, 2017; Eagle et al, 2017; Graham et al, 2018) and should be considered when assessing the environmental impact of EEF use.…”
Section: Examining the Kanter And Searchinger Papermentioning
confidence: 99%
“…A recent meta‐analysis reported that a 1°C change in average July temperature was equivalent to the difference in losses related to the use of nitrification inhibitors with higher losses as temperature increases (Eagle et al, 2017). Research conducted in Illinois through the 2015, 2016, and 2017 growing seasons compared three EEF nitrogen products to no N fertilizer and the standard practice of injecting anhydrous ammonia (Graham et al, 2018). Nitrous oxide emissions from the plots, which received the same rate of 180 lb N/ac, varied within and across years for the three products (Graham et al, 2018).…”
Section: Examining the Kanter And Searchinger Papermentioning
confidence: 99%
See 3 more Smart Citations